2021
DOI: 10.1088/1742-6596/2106/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial autocorrelation analysis of Covid-19 cases in South Kalimantan, Indonesia

Abstract: Coronavirus Disease 2019 (COVID-19) is a new coronavirus that was discovered in Wuhan, China, at the end of 2019. In March 2020, the outbreak extended throughout the world, including Indonesia and one of its provinces, South Kalimantan. This rapid expansion should belinked to people’s mobility between regions, hence the linkage across regions must be examined. In South Kalimantan Province, the purpose of this research is to evaluate the distribution and relationship across regions in terms of the number of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The most commonly used method in the existing literature is Moran’s I [ 42 ]. Greater than 0 indicates positive correlation, less than 0 indicates negative correlation.…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly used method in the existing literature is Moran’s I [ 42 ]. Greater than 0 indicates positive correlation, less than 0 indicates negative correlation.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this investigation revealed the adoptable functionality of spatial autocorrelation in disease modeling. To evaluate the spatial distribution and relationship neighboring the regions in terms of the COVID-19 outbreak, Amaliah et al ( 2021 ) used Moran’s I Index. Considering the results of this research, a spatial autocorrelation of the confirmed cases is detected.…”
Section: Introductionmentioning
confidence: 99%
“…It is documented for us by studies that are published in various regions of the world. As an example, we present studies from Italy [ 8 , 9 , 10 ], Turkey [ 11 ], Algeria [ 12 ], India [ 13 ], Indonesia [ 14 ], Kuwait [ 15 ], China [ 16 ], and Canada [ 17 ]. In the space of the V4 countries, contributions were made from the environment of the Czech Republic [ 18 , 19 , 20 ], Poland [ 21 ], Hungary [ 22 , 23 ], and Slovakia [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%